Eco-marxism and the politics of natural resource extractivism: The case of South America - Tomic, Milos; Kesić, Dušan (Sociološki pregled, 2025)
The paper analyzes the theoretical positions of eco-Marxism with a special focus on the current policy of extractivism of natural resources localized in the territory of South American countries. The aim of the research is an attempt to identify and systematically describe the capitalist exploitation of human labour and a series of environmental problems that arise as a consequence of the exploitation of nature. A complementary methodological approach was applied that includes actor analysis and desk analysis. The research results indicate that Latin American countries are increasingly becoming “victims” of the so-called ecological imperialism, where the lack of appropriate national institutions leads to the collapse of the state system with pronounced social dystropies.